EDUCATION OF YOUNG GENERATION-KEY TO HAPPINESS - Abdurahim Khasanovich Khasanov (Galaxy International Interdisciplinary Research Journal, 2022)
In given article the basic features and methods of increase of spiritually-moral shape of youth in a civil society in the conditions of Uzbekistan are considered.